2018
DOI: 10.1038/s41598-018-33812-1
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × Environment interactions of Nagina22 rice mutants for yield traits under low phosphorus, water limited and normal irrigated conditions

Abstract: Multi environment testing helps identify stable genotypes especially for adverse abiotic stress situations. In the era of climate change and multiple abiotic stresses, it becomes important to analyze stability of rice lines under both irrigated and stress conditions. Mutants are an important genetic resource which can help in revealing the basis of natural variation. We analyzed 300 EMS induced mutants of aus rice cultivar Nagina22 (N22) for their G × E interaction and stability under low phosphorus (P), water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…Rita et al [23] studied G × E interaction for 14 genotypes for yield and its component traits. G × E interactions for yield traits in rice using mutant populations were previously reported by Poli et al [24] and Oladosu et al [25]; such interactions for seed yield in chickpea were reported by Atta et al [26].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Rita et al [23] studied G × E interaction for 14 genotypes for yield and its component traits. G × E interactions for yield traits in rice using mutant populations were previously reported by Poli et al [24] and Oladosu et al [25]; such interactions for seed yield in chickpea were reported by Atta et al [26].…”
Section: Introductionsupporting
confidence: 56%
“…Five plants at random were taken from each plot in each replication under each environment to record the nine yield-related traits. Biometric observations were recorded using the methodology employed by Poli et al [24] in rice and Rita et al [23] in blackgram. As per the model described by Zobel et al [30] and Crossa [31], the AMMI analysis was employed to evaluate associations between genotypes, environment, and G × E interaction.…”
Section: Evaluation Gei and Stability Of Mutant Lines For Grain Yieldmentioning
confidence: 99%
“…The existence of crossover and non-crossover GEI in multi-environment testing is widespread, especially in multi-location trials 27 . Which-won-where graphs of GGE biplot address different factors like crossover GE, mega-environment differentiation and specific adaptation 24 , 28 – 30 . Based on GGE biplot analysis, the testing environments were classified into three mega-environments, comprising early (E1A and E2A), medium (E1B and E2B) and late (E1C and E2C).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the study on yield stability and G x E interaction necessitates the consistency of chickpea grain yield to develop a variety that respond optimally and reliably in different environmental conditions over the years [9]. Hence, the effects of G x E interaction to be considered for the development of variety [10]. In order to estimate G x E interaction, the stability analysis can be examined in replicated trails over various environments following environment wise analysis of variance.…”
Section: Introductionmentioning
confidence: 99%